In vitro model systems for host-microbiota interaction studies - R. Inciuraite; G. Varkalaite; J. Skieceviciene; J Skieceviciene; U. Kulokiene (Microbiota in Health and Disease)
Despite the efforts to explore the communication between the human gut and intestinal microbiota in recent years, the complexity of this interaction remains not fully understood. This is mostly due to a lack of mechanistic insights into how this interspecies relationship works. However, ongoing work in the employment of various in vitro systems provides an excellent opportunity to understand the role of different components in host-microbiota signaling. This work provides a structured review of the most used in vitro model systems for the exploration of host-microbiota interactions in health and disease published in the last year. The data presented uncovers the variety of available models, such as immortalized cell monocultures, 3D epithelial organoids and their monolayers, co-cultures, gut-on-a-chip platforms, scaffolds, etc., and their applications in different scientific contexts. Future studies are needed to deepen the understanding of the interplay between gut mucosa and microbial communities, improve the existing in vitro systems, and develop new experimental platforms.